1430Guideline-based cardiovascular disease risk assessment among Indigenous Australians in a general practice setting. (2nd September 2021) - Koye, Digsu; Lamb, Karen; Lee, Ping-Wen; Kotevski, Aneta; Haurat, Javier; Turner, Maureen; Ebsworth, Gabrielle; Druce, Tanya; Bryant, Karen; Price, Eloise; Taylor, Georgia; Simpson, Julie; et al.
Abstract: Background: HealthGap is a population-based cohort study aiming to understand health inequities in cardiovascular disease (CVD) risk between Indigenous and non-Indigenous Australians. We examined guideline-based CVD risk assessment in Victoria. Methods: NPS MedicineInsight, the largest Australian primary health care dataset, provided data on CVD risk factors (age, gender, smoking status, diabetes, systolic blood pressure (SBP), total and HDL cholesterol) and Aboriginal or Torres Strait Islander (Indigenous) status. The percentage of patients who had all risk factors measured was calculated and compared by Indigenous status. Results: In total, 7, 928 of 1, 435, 111 patients were classified as Indigenous. The percentage of patients with measured cholesterol was slightly lower for Indigenous (total cholesterol=31.4%, HDL=26.9%) than non-Indigenous patients (total cholesterol=35.6%, HDL=31.8%). However, more Indigenous patients had SBP measured (65.6% vs. 59.8%). Diabetes diagnosis was higher among Indigenous patients (6.2% vs. 3.6%). There was a small difference in the proportions with all risk factors measured between Indigenous and non-Indigenous patients (24.1% vs. 26.6%). Among Indigenous patients aged at least 35 years who should have had their risk assessment measured, 41.9% had all risk factors measured, while 50.7% of the non-Indigenous Australians (aged ≥45 years) had all risk factors measured. Conclusions: Overall, the proportion of people with all CVD risk factors measured was smaller for Indigenous compared to non-Indigenous people. Key messages: Fewer than half of Indigenous Australians have CVD risk factors captured in a primary health care setting. This has implications for health care policy and programs seeking to improve CV health outcomes among Indigenous Australians.